Pruritus and brain tumours: A prospective and descriptive study - Marie‐Anne Fardel; Emilie Brenaut; Dewi Guellec; Maxime Etienne; Maxime Fouchard; Romuald Seizeur; Laurent Misery (Wiley, 2023)
Abstract Background Pruritus, especially localised to the nostrils, has been reported as a specific sign of brain tumours. Objectives The main goal of this study was to estimate the prevalence of pruritus in a group of patients with brain tumours. The second outcome was to better characterise this pruritus with a specific questionnaire and a skin examination. Methods From June 2020 to September 2021, all patients with a diagnosis of brain tumour were included in this prospective, monocentric study. If the patient suffered from pruritus, a dermatological examination was performed. Results Two hundred patients with brain tumours were included. Thirty‐five of them suffered from pruritus (17.5%). Among them, 15 patients did not present with any skin disease, and 8 could have neuropathic pruritus according to the NP5 questionnaire. No patients presented with pruritus of the nostrils. Discussion This study did not show clear evidence of specifically localised pruritus induced by brain tumours. Conclusion Pruritus observed in patients with brain tumours seems not to be caused by the brain malignancies in most cases. The specific localization to the nostrils cannot be considered a specific marker.